Level of personality functioning and its relationship with core schemas in anxiety and mood disorders - Naumova, Katerina; Naumov, Florijan (My University, 2022)
The DSM-5 Alternative model for personality disorders initiated a growing body of research on deficits in self-functioning and interpersonal relatedness. However, fewer studies have focused on personality impairments in anxiety and mood disorders. Furthermore, cognitive theory proposes that core beliefs, primarily negative self-schema, determine the development and maintenance of personality dysfunction. Thus, the objective of this study was to examine the severity of personality psychopathology in anxiety and mood disorders and its relationship with core beliefs about self and others. The participants were outpatients (N = 92, mean age: 28.6 years) diagnosed with anxiety disorders, mood disorders and mixed anxiety and depressive disorder. A demographically matched community sample (N = 92, mean age: 30.2 years) was included as a comparison group. Both samples completed the LPFS-BF 2.0, a measure of impairments in self and interpersonal functioning and the Brief Core Schema Scales that assess global negative and positive self and other evaluations. As expected, disturbances in self and interpersonal functioning were significantly higher in outpatients relative to controls. Outpatients also endorsed significantly less positive beliefs about self and others and significantly more negative self-beliefs. However, they did not differ significantly from controls in negative beliefs about others. Hierarchical multiple regression analyses revealed that after controlling for the effects of gender and age, only negative self-schema was a significant predictor of impaired self-functioning among outpatients, while both negative self and negative other schemas predicted impaired interpersonal functioning. The findings are in line with the cognitive model of personality disorders and highlight the need to assess personality functioning before and during treatment of anxiety and mood disorders.
Keywords: Personality functioning; Core beliefs; Negative self-schema; Personality disorders